Revitalization of Indigenous Language of Boyolali By Spoken Habituation In Society Contexts - Herlambang Gilang Setyo Nugroho; Luky Budhi Utomo; Ildre Revansha Muhar; Daning Nur Setyowati (LADU: Journal of Languages and Education, 2022)
Background:  Culturally, language is a one of the cultural elements of a society. Therefore, it is stated that language is a manifestation of the identity of the speaker community. By expressing or explaining something, researchers communicate using different points of view and ways. In the era of globalization, the view of life and modern human interaction has undergone rapid and dynamic changes so that local languages ​​are starting to be forgotten in their use because they are considered obsolete and tacky. The younger generation in urban and rural areas likes to use urban slang in their daily routine interactions. Purpose: This study aims to preserve the smooth Javanese language in daily life. Design and methods: Researchers used qualitative phenomenology method in this study to find social facts in the community. The data are gathered using documentary acquisition techniques by observation and in the form of a qualitative descriptive design. The researcher made a documentary film about efforts to maintain regional languages ​​in social life using shooting methods consisting of Development procedures, Pre-Production procedures, Production procedures, Post Production procedures, and Distribution procedures. Results: The results that the researchers produced Bahasaku documentary film containing efforts to maintain local languages ​​in social life and uploaded them on social media YouTube. This is because YouTube is a social media that is currently easily accessible and has many users.